DBT degradation enhancement by decorating Rhodococcus erythropolis IGST8 with magnetic Fe3O4 nanoparticles - Ansari, Farahnaz; Grigoriev, P.; Libor, Zsuzsanna; Tothill, Ibtisam E.; Ramsden, Jeremy J. (Wiley-Blackwell, 2009)
Biodesulfurization (BDS) of dibenzothiophene (DBT) was carried out by Rhodococcus erythropolis IGST8 decorated with magnetic Fe3O4 nanoparticles, synthesized in-house by a chemical method, with an average size of 45-50 nm, in order to facilitate the post-reaction separation of the bacteria from the reaction mixture. Scanning electron microscopy (SEM) showed that the magnetic nanoparticles substantially coated the surfaces of the bacteria. It was found that the decorated cells had a 56% higher DBT desulfurization activity in basic salt medium (BSM) compared to the nondecorated cells. We propose that this is due to permeabilization of the bacterial membrane, facilitating the entry and exit of reactant and product, respectively. Model experiments with black lipid membranes (BLM) demonstrated that the nanoparticles indeed enhance membrane permeability.
Keywords: Biodesulfurization; Dibenzothiophene; Rhodococcus erythropolis; Magnetic Fe3O4; Nanoparticles; Black lipid membrane